The Start-Up Survival Guide: What You Need to Know to Make It Through the First Three Years - Chris Lilly (New York Prentice Hall, 2006)
There are serious challenges that face every entrepreneur as they start up their own business and common mistakes that often trip them up. You don't have to learn the hard way: 'The Start-Up Survival Guide' will ensure that you know what the common pitfalls are and how to avoid them.
Age Group: Adult
Includes bibliographical references and index.
Keywords: New Business Enterprises; Management; Small business; New Business Enterprises -- Management -- Handbooks, Manuals, Etc; Small Business -- Management -- Handbooks, Manuals, Etc